Rancang Bangun Sistem Manajemen Produksi dan Distribusi di Konveksi Berbasis Web App (PWA) - Fajri Alamsyah; Ahmad Selao; Andi Wafiah; Masnur; Syahirun Alam; Muh. Zainal (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2026)
This study develops a Progressive Web App (PWA)-based production and distribution management system for garment industries, aiming to enhance operational efficiency and production process transparency. The designed system integrates all production stages—from raw material planning, production scheduling, task allocation, to quality control—featuring real-time monitoring accessible across multiple devices. Using a quantitative approach with development research design, the study involved 30 end-users (10 production managers and 20 garment workers). Data was collected through Likert-scale questionnaires and in-depth interviews, analyzed via descriptive statistics and thematic methods. Evaluation results show average scores of 4.2/5 for usability, 3.8/5 for system security, and 4.0/5 for user satisfaction. Technical testing demonstrated average response time of 1.2 seconds, load time of 2.8 seconds, and offline capability up to 72 hours. Key findings reveal that 85% of respondents rated the app as user-friendly with an intuitive interface, while 78% reported improved team coordination efficiency. However, technical challenges were identified, particularly in data security (only 65% found security features adequate) and limited analytics for strategic decision-making. This research provides practical contributions through affordable technology solutions for small-scale garment businesses, while identifying development areas: (1) multi-factor authentication integration, (2) enhanced offline data backup systems, (3) service worker caching strategy optimization.